Adoption of electronic-cigarette-free, hookah-free and American College Health Association recommended tobacco-free policies among a national sample of postsecondary educational institutions. Issue 1 (2nd January 2020) - Bayly, Jennifer; Trad, Catherine; Saint-Fort, Launick; Andrews, Mary; Patel, Minal; Haynie, Denise; Simons-Morton, Bruce; Choi, Kelvin
Abstract: Objective: To examine the prevalence of various types of tobacco-free policies among a US national sample of postsecondary educational institutions (PEIs). Participants: A national sample of US PEIs ( N = 605) attended by the participants of the NEXT Generation Health Study. Methods: Tobacco policies of these PEIs were reviewed to determine if they were e-cigarette-free (yes/no), hookah-free (yes/no), and ACHA-recommended tobacco-free (yes/no) in June–December 2017. Logistic regression models were used to examine the relationships between institutional characteristics and tobacco policies. Results: Overall, 39.2, 26.0, and 20.0% of the sample adopted e-cigarette-free, hookah-free, and ACHA-recommended tobacco-free policies, respectively. Proprietary PEIs (vs. public) were less likely to have ACHA-recommended tobacco-free policies, while PEIs in the South and Midwest (vs. West) were more likely to have ACHA-recommended tobacco-free policies ( p < 0.05). Conclusions: Most sampled PEIs did not have ACHA-recommended tobacco-free polices. Subsequent research needs to investigate how ACHA-recommended tobacco policies influence tobacco use.